Thermal Analysis of Honeycomb Sandwich Panel - Sonawane, Mr. K.R. (Journal of Advanced Research in Glass, Leather and Plastic Technology; Vol 3 No 1 (2020): Journal of Advanced Research in Glass, Leather & Plastic Technology, 2021)
Heat-transfer analysis has been performed on sandwich warm security framework (TPS) for future vehicles. The structures are manufactured from slim walled metal sheets. These manufactured structures are important for the air outline external cover give warm assurance to the inside parts mounted inside the vehicle. The temp assurance framework materials utilized for sandwich structures ought to have high strength even at raised temperatures. It is simpler to recreate the 1500 C temperature on the Aluminum sandwich structures and discover the temperature inclination over the sandwich profundity. Examination was done on hexagonal structure honeycomb cell, the ANSYS investigations have been accomplished for both square cell board and hexagonal honeycomb board for correlation. Trials we led on Aluminum combination honeycomb sandwich boards and the approvals of test work utilizing ANSYS investigation have been performed. The ANSYS demonstrating accomplished for both, the square and hexagonal honeycomb sandwich boards of the Aluminum compound. This paper center the warmth move investigation and in investigating the approaches to decrease the warmth move impact with the techniques referenced above, which would be successfully utilized for flight vehicle applications. How to cite this article: Sonawane KR, Sangale UV. Thermal Analysis of Honeycomb Sandwich Panel. J Adv Res Glass Leath Plast Tech 2020; 3(1): 18-26